Rehabilitation of waste materials near lead and zinc mining sites in Galena, Kansas - Alghamdi, Abdulaziz Ghazi (Kansas State University, 2016)
The abandoned lead (Pb) and zinc (Zn) mines in the Tri-State Mining District of Kansas, Missouri, and Oklahoma have left a legacy of environmental contamination. The waste materials are highly polluted, not only with Pb and Zn, but also cadmium (Cd), which often co-occurs geologically with Zn. The District includes Galena, Kansas, where mines operated between 1876 and 1970. Because limited information exists concerning these mines, three studies were done to characterize them and to investigate a way to remediate the mine waste materials. In the first study, the physical characteristics of the mine waste materials were determined. Plots at Galena that had been established by researchers in May 2006 were sampled in November 2014, 8.5 years after they had received amendments (combinations of compost, lime, and bentonite). Water content, bulk density, infiltration rate, unsaturated hydraulic conductivity, aggregate stability, and particle size distribution were determined. The physical characteristics were highly variable, and the amendments added 8.5 years earlier had no effect on them, except the wind erodible fraction (fraction <0.84 mm in diameter) which was low on treatments that contained bentonite. Because biosolids had never been applied to the mine waste materials at Galena for remediation, an experiment was done to see their effect on plant growth and availability of heavy metals. In 2014 the plots established in 2006 were sampled and a greenhouse study was set up with sudex [Sorghum bicolor (L.) Moench x S. Sudanese (P.) Staph]. Plants grew in the mine waste materials with and without biosolids, and 110-111 days after planting the roots, shoots, and heads with grain were harvested and analyzed for heavy metals. At the same time, the mine waste materials were analyzed for heavy metals, organic carbon (C), nitrogen (N), and phosphorus (P). Plants grew better with biosolids than without biosolids, and only the plants grown with biosolids produced heads . Plants grown without biosolids were stunted and showed severe heavy metal toxicity. Organic C and P were increased in the mine waste materials after the addition of biosolids. Thus, the biosolids increased organic C and P, and they apparently made the heavy metals less available for plant uptake. Many studies have shown the importance of attic dust in documenting metal pollution from a mine. Attic dust in Galena had never been studied, so in a third experiment, 14 dust samples in Galena were collected from interiors (attics and one basement) of nine different buildings using two methods: sweeping with a brush and vacuuming. Dust samples were analyzed for heavy metals (Cd, Cu, Fe, Mn, Ni, Pb, and Zn), mineralogy using X-ray diffraction (XRD), scanning electron microscopy (SEM) in conjunction with energy dispersive spectroscopy (EDX), and particle size. Concentrations of Cu, Fe, Mn, Ni, and Zn in the dust were higher than in the mine waste materials. The results from XRD agreed with those from the SEM-EDX analysis. About 10% of each dust sample contained particulate matter (PM) with a diameter of less than 10 μm (PM₁₀), which is a health concern.
Keywords: Attic dust; Physical properties; Mine waste materials; Lead; Zinc; Rehabilitation